Understanding the Unlawful Acts (Problems and Challenges) A Book Review 'Perbuatan Melanggar Hukum', Prof. Dr. R. Wirjono Prodjodikoro, SH., CV Mandar Maju, Bandung, 108 Pages, ISBN 978-979-538-470-0 - Nababan, Natanael Andra Jaya (Indonesian Journal of Advocacy and Legal Services, 2020)
Book witen by Prof Dr. R. Wirjono Prodjodikoro, Wirjono was bor in Surakarta, Dutch East Indies, on 15 June 1903. After completing his primary education, he attended the Rechtsschool I in Batavia, graduating in 1922. He then became a judge, later taking time to study at Leiden University in Leiden, Netherlands. This book talks about acts that can violate laws which are viewed from the point of civil law. I The term "unlawrful acts" in general is very broad meaning that is if the word "law" is used in the broadest sense and the matter of legal conduct viewed from all angles. Now the act of violating the law will be discussed smply because there are consequences and solutions that are regulated by the Civil Code in the broadest sense, which includes commercial law. This needs to be stated I here, because Article 102 of the Provisional Constitution distinguishes Civil Law from Commercial Law.